Multicriterial, multiparameter optimization of axial recycling turbo-expander units - Novikov, Maksym (National Technical University "Kharkiv Polytechnic Institute", 2024)
This study gathered key parameters from 93 gas distribution stations and proposes conducting scientific research to explore the feasibility of employing multicriterial multiparameter optimization for the flow components of axial turbines, considering operational conditions, and leveraging existing operational turboexpander units. Using new methods and methods of modern achievements of science and technology is a key task for today's moment. It is proposed to carry out scientific research work on finding the possibility of using multicriterial multiparameter optimization of the flow parts of axial turbines taking into account the operating modes, on the basis of utilization turbo-expander units that are already in operation.
Keywords: optimization; turboexpanders; national energy independence; power supply; turboexpander power plants